Integrated miRNA and mRNA profiling of tumor‐educated macrophages identifies prognostic subgroups in estrogen receptor‐positive breast cancer. Issue 1 (16th August 2014) - Bleckmann, Annalen; Leha, Andreas; Artmann, Stephan; Menck, Kerstin; Salinas-Riester, Gabriela; Binder, Claudia; Pukrop, Tobias; Beissbarth, Tim; Klemm, Florian
Abstract : Introduction: Various studies have identified aberrantly expressed miRNAs in breast cancer and demonstrated an association between distinct miRNAs and malignant progression as well as metastasis. Even though tumor‐associated macrophages (TAM) are known mediators of these processes, little is known regarding their miRNA expression upon education by malignant cells in vivo. Methods: We profiled miRNA and mRNA expression of in vitro tumor‐educated macrophages (TEM) by indirectly co‐culturing with estrogen‐receptor‐positive (ER+) MCF‐7 breast cancer cells. The prognostic power of the resulting miRNA list was investigated in primary breast cancer datasets and compared to other signatures. Furthermore, miRNA expression levels were correlated to mRNA expression of macrophage markers and the impact on prognosis was assessed. Results: Through the evaluation of the group effects between differentially‐expressed miRNAs and their target mRNAs in TEM, the power of detecting regulated miRNAs was greatly increased. The resulting list of 96 miRNAs predicts disease‐free survival (DFS) in external datasets of ER+ breast cancer patients and performs well in comparison with other miRNA signatures. Clustering with the predefined miRNA list revealed a significant difference in survival between the two resulting patient groups. Furthermore, an optimized miRNA list, based on correlations with macrophages markers, proved even more capable at identifying patient clusters significantly differing in DFS. Conclusions: In vitro profiling of TEM and subsequent bioinformatic verification identified miRNAs with a high prognostic power for DFS when transferred into the clinical setting of primary breast cancer. The resulting miRNAs not only verify previously established findings but also lead to new prognostic markers. Furthermore, our data suggest that TAM contribute to the total miRNA expression profile of ER + breast cancers. Highlights: miRNA and mRNA were measured in macrophages exposed to ER + breast cancer cells. Regulated miRNAs were detected by analyzing group effects of mRNA targets. The resulting miRNA list has good prognostic value for DFS in ER + breast cancer. Correlation of miRNAs to macrophage markers improved identification of clusters differing in DFS.